The Role of Cooperative in Increasing the Economic Independence of Islamic Boarding Schools - Ramadhan, Narendra Jumadil Haikal; Salsabila, Nilla Putri; Murni, Wahid; Zuhroh, Ni'matuz (IAIN Manado, 2024)
This study aims to explore: (1) the role of cooperatives in increasing the economic independence of Islamic boarding schools, (2) obstacles and challenges faced in increasing economic independence, and (3) strategies in increasing economic independence. A qualitative approach with a case study research type was applied to the At-Ta'awun cooperative at the DDI Mangkoso Islamic Boarding School, Barru Regency. Data collection through interviews and observations, data analysis using data condensation patterns, data presentation, and drawing conclusions. The technique of checking the validity of findings using triangulation techniques and source triangulation. The results showed that (1) the cooperative has a vital role in increasing the economic independence of the Islamic Boarding School by contributing to the welfare of santri, teachers, and the surrounding community, (2) several obstacles and challenges that need to be overcome, such as difficulties in harmonizing cooperative rules, limited resources, and lack of management and technology expertise, and (3) innovative and proactive strategies, such as cooperation with other Islamic Boarding School and employee development, the cooperative continues to strive to strengthen the economic independence of the Islamic Boarding School.